2021
DOI: 10.3390/vaccines9080907
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Maternal to Neonate Transfer of Neutralizing Antibodies after SARS-CoV-2 Vaccination with BNT162b2: A Case-Report and Discussion of the Literature

Abstract: This case reports on the successful maternal to fetal transfer of neutralizing antibodies after vaccination with BNT162b2 in a pregnant woman at 25 weeks of gestation. The levels of neutralizing antibodies were approximately 5-fold higher in the umbilical cord than in the maternal blood while the level of total antibodies showed only a 2-fold increase. This suggest that the antibodies that crossed the syncytiotrophoblast cell barrier have specific characteristics that correlate to functional neutralizing capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…A flowchart of study selection process is reported in Figure 2 . We considered 46 records: 30 of them included pregnant mothers [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], two studies included both pregnant and lactating mothers [ 39 , 40 ], and 14 studies included lactating mothers [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Most studies were conducted in the United States (41.3%) and Israel (26.1%), along with three in Italy (6.5%), two in Spain (4.3%) and in Poland (4.3%), and the remaining (17.2%) in the United Kingdom, Qatar, Belgium, Germany, Norway, Portugal, the Netherlands, and Singapore.…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart of study selection process is reported in Figure 2 . We considered 46 records: 30 of them included pregnant mothers [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], two studies included both pregnant and lactating mothers [ 39 , 40 ], and 14 studies included lactating mothers [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Most studies were conducted in the United States (41.3%) and Israel (26.1%), along with three in Italy (6.5%), two in Spain (4.3%) and in Poland (4.3%), and the remaining (17.2%) in the United Kingdom, Qatar, Belgium, Germany, Norway, Portugal, the Netherlands, and Singapore.…”
Section: Resultsmentioning
confidence: 99%
“…[46] However, impaired placental transmission during the third trimester has been recorded [46,47]. Therefore, late second trimester may be proposed as a perfect time for vaccination [48], although further evaluation of this is needed.…”
Section: Resultsmentioning
confidence: 99%
“…The role of these passively acquired antibodies in protecting infants is the subject of ongoing investigation. To date, there is no evidence these antibodies cause ADE/MISC in infants [ 65 ].…”
Section: The Role Of Antibodies In the Pathogenesis Of Various Covid-...mentioning
confidence: 99%